Ranganathan’s Contributions to Knowledge Organization and Presentation - Raghavan, K. S.; Neelameghan, A. (Journal of Information and Knowledge, 2013)
Knowledge Organization tools can be used for a variety of purposes including arranging information objects, representation of their aboutness, displaying semantic relations between concepts and even for presentation of ideas in texts. The paper highlights some of the major contributions of Ranganathan to the theory and practice of knowledge organization.